2019 novel coronavirus disease with secondary ischemic stroke: two case reports - Bin Fu; Yun Chen; Ping Li (BMC Neurology, 2021)
Abstract Background The COVID-19 pandemic, which broke out in Wuhan in 2019, has become the global health crisis of our time. Elderly patients with certain fundamental diseases are more likely to develop severe cases. The secondary lesion following viral infection have only rarely been reported. Case presentation We here report two cases of coronavirus-infected pneumonia with acute ischemic stroke in middle-aged patients. In both COVID-19 cases, neurological physical examinations showed normal results before infection. Lymphocytopenia, accompanied by elevated cytokines and D-dimers, were found from serum clinical laboratory examination at admission. Dysarthria and limb muscle weakness are initial manifestations, occurring one week after infect-causative pathogen, SARS-CoV-2. The head CT and head/neck arterial CTA showed small-vessel occlusion. The patients were diagnosed with coronavirus diseases with secondary acute ischemic stroke. They were treated with tirofiban and followed up with daily aspirin and atorvastatin. Conclusions These cases suggested that secondary ischemic stroke, mainly manifested as small-vessel occlusion, should be considered for COVID-19 patients and diagnosed and treated promptly.